De-escalation of radiation therapy in patients with stage I, node-negative, HER2-positive breast cancer - Jose G. Bazan (Nature Portfolio, 2021)
Abstract In the modern era, highly effective anti-HER2 therapy is associated with low local-regional recurrence (LRR) rates for early-stage HER2+ breast cancer raising the question of whether local therapy de-escalation by radiation omission is possible in patients with small-node negative tumors treated with lumpectomy. To evaluate existing data on radiation omission, we used the National Cancer Database (NCDB) to test the hypothesis that RT omission results in equivalent overall survival (OS) in stage 1 (T1N0) HER2+ breast cancer. We excluded patients that received neoadjuvant systemic therapy. We stratified the cohort by receipt of adjuvant radiation. We identified 6897 patients (6388 RT; 509 no RT). Patients that did not receive radiation tended to be ≥70 years-old (odds ratio [OR] = 3.69, 95% CI: 3.02–4.51, p < 0.0001), to have ≥1 comorbidity (OR = 1.33, 95% CI: 1.06–1.68, p = 0.0154), to be Hispanic (OR = 1.49, 95% CI: 1.00–2.22, p = 0.049), and to live in lower income areas (OR = 1.32, 95% CI: 1.07–1.64, p = 0.0266). Radiation omission was associated with a 3.67-fold (95% CI: 2.23–6.02, p < 0.0001) increased risk of death. While other selection biases that influence radiation omission likely persist, these data should give caution to radiation omission in T1N0 HER2+ breast cancer.